Characteristics of Offender’s Personality who Committs False Suggestion of the Court or Other Authorized Agency - K. S. Kotlubaeva (Law and Safety)
Particular attention has been paid on the necessity and urgency of developing a methodology for investigating the false suggestion of the court or other authorized agency, where a compulsory element of the criminalistic characteristic is the offender’s personality.